Applied stochastic modelling - Morgan, Byron J.T. 1946- (Arnold texts in statistics, 2000)
The last 30 years have seen many exciting major developments in the theory and practice of statistics. This new book is a senior undergraduate and postgraduate text covering many of the most important of these advances. As well as covering modern techniques, the material of the book integrates and revises standard probability and statistical theory. As much modern statistical work is implemented using a computer, over 50 short MATLAB programs are incorporated in the book." "This text provides a thorough grounding in the construction, fitting and evaluation of statistical and stochastic models. It is written by one of the leading authorities in the field, who has had great success teaching this material at a variety of levels.